Analisis Efisiensi Saluran Pemasaran Ikan Teri (Stolephorus sp.) di Desa Sanggalangit, Kabupaten Buleleng - Lingga Nurmalasari; I Wayan Restu; I Ketut Wija Negara; I Wayan Sudana (Program Studi Manajemen Sumberdaya Perairan, Fakultas Kelautan dan Perikanan, Universitas Udayana, 2021)
The location for the research is decide in Sanggalangit Village, Gerokgak District, Buleleng Regency, Bali. The highest production species in the coast of Sanggalangit Village, Buleleng Regency is Anchovy. The village is chosen because there are a lot of fisherman whos active to catch and do the Anchovy’s marketing. The aim of this research is to know the condition of marketing channels and analysis the marketing channels efficiency of Anchovy in Sanggalangit Village. This research is held on December 2019 until January 2020 with qualitative and quantitative methods by observation and interviews. Interviewed with the fisherman, the institution of marketing such as the collecting trader and the retailer. The share margin analysis and farmer’s share as a tool to know the marketing channels efficiency. The marketing channels that occurs in Sanggalangit Village is from the fisherman, to the collecting trader and then to the retailer, until to the customer’s hand. The share margin from this Anchovy’s marketing channels is obtained Rp. 13.000/kg where the margin from the fisherman with the collecting trader is Rp. 3.800 and the margin from the collecting trader with the retailer is obtained Rp. 9.200/kg. The amount of farmer’s share is 56,67 %. The marketing efficiency value is 15,18 %, which is mean the marketing channels efficiency of Anchovy in Sanggalangit Village is efficient.